Formalization of risk management in the context of digital business transformation - Koshekov Kairat; Alibekkyzy Karlygash; Toiganbayev Beglan; Belginova Saule; Keribayeva Talshyn; Tulaev Viktor; Koshekov Abai (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The aim of the article is to develop a formal methodology for quantitative assessment of the quality of аcontrol in a closed system with feedback in the context of digital transformation. In the proposed study, attention is focused on assessing the quality of management in organizational and technical systems on the example of the aviation industry. The following hypotheses were adopted in the study: in the digital management of business processes of an economic entity, the role of intellectual support is acquired by methods of formal description of processes: control, decision-making and corrective action on the control object. In critical situations, the psychotype of the person making the decision acquires a decisive role. The study solves two scientific and practical problems: development of a formal method for quantitative assessment of the quality of management of a complex multi-criteria organizational and technical system under the conditions of statistical uncertainty of management agents, taking into account feedback in the management of an object; formalization of the process of quantitative assessment of decision-making risks in the environment of statistical uncertainty of control agents and psychological factors of the decision maker.